INCREASING STUDENTS' LEARNING OUTCOMES IN CHRISTIAN RELIGIOUS EDUCATION LESSONS AND CHARACTERISTICS OF GOD'S MAIN WORKS IN MULTIPURPOSE - Enita Simatupang (Sean Institute, 2022)
Improving student learning outcomes in Christian religious education lessons and character, the subject matter of God's work in diversity in class X mia 1 even semester of SMA Negeri 9 Medan through creative problem solving learning for the 2020/2021 school year. The purpose of this study was to improve student learning outcomes in Class XMIA 1 SMA Negeri 9 Medan in the 2020/2021 academic year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are students of Class X MIA 1 SMA Negeri 9 Medan as many as 21 people, the instrument used to obtain data is by using tests, observing the range of values ​​for the test. are the highest and lowest values. The instrument used for data processing is to calculate the number of students' scores that have not reached the KKM and the scores that have reached the KKM. The KKM has been determined, namely 75. The results of this study indicate that there is an increase in learning outcomes using the Creative Problem Solving Method with the following results: There is an increase in the average learning outcomes of students, where in the initial test the average learning outcomes of students are 44, 76, in the first cycle increased to 68.57 then in the second cycle increased again to 75.23. There was an increase in the number of students who completed, where in the initial test the number of students who completed only 0%, increased to 71% in the first cycle then increased again to 95% in the second cycle There was a decrease in the number of students who did not complete.